The Duration of the Alcohol Hangover - Marith van Schrojenstein Lantman; Marlou Mackus; Joris C Verster (Journal of Addiction Disorder and Rehabilitation, 2018)
Introduction and aims Previous research has focused primarily on the severity of the alcohol hangover. Much less is known about the duration of the alcohol hangover. The objective of this analysis was to examine the average duration of the alcohol hangover. Design and Methods N=811 Dutch students, aged 18-30 years old, completed a survey on alcohol consumption and their latest alcohol hangover. Overall hangover severity was reported for every two hours after waking up (starting 4am until midnight). Hangover duration was calculated from the moment of stopping alcohol consumption until the first time hangover severity scores reached zero. Results During the drinking session that resulted in their latest hangover they consumed a mean (SD) of 5.9 (6.2) alcoholic drinks, followed by 6.5 (2.0) hours of sleep. The start of the alcohol hangover was not assessed, as it can be assumed that BAC approached zero while participants were sleeping. From the moment of stopping alcohol consumption, the average duration of the alcohol hangover was 18.4 (3.8) hours. For the majority of drinkers, hangover duration ranged from 14 to 23 hours. Alternatively, the hangover lasts approximately 12 hours from the time of waking up. Hangover duration correlated significantly with hangover severity and total sleep time, but no significant association was found with the number of alcoholic drinks that were consumed. Discussion and Conclusions The duration of the alcohol hangover ranged from 14 to 23 hours, with an average of 18.4 hours after stopping drinking, or alternatively, about 12 hours after waking up.
Keywords: alcohol